PERLINDUNGAN HUKUM NOTARIS DALAM PERJANJIAN JUAL BELI TANAH - Yana Sukma Permana (The Juris, 2022)
That Indonesia is a State of Law (Rechstaat) that upholds the principles of the rule of law, namely the principle of guaranteeing certainty, order, and legal protection with the core of truth and justice. Notary is a public official who is authorized to make authentic deeds and other authorities, which are determined by the position of a notary as a public official as regulated in Law Number 30 of 2004 concerning Notary Positions as amended by Law Number 2 of 2014 Position of Notary. Article 20 paragraph (2) of the UUPA states: "Property rights can be transferred and transferred to other people", but in the transition it is not immediately transferred like buying and selling other goods. Even though there is a contract in the sale and purchase of land, the status of ownership cannot simply change.